Evolução da distribuição do tamanho de partículas na floculação de água de baixa turbidez - Mendes, Yuri Cardoso (2017)
The aim of this work was evaluate the flocculation process in low turbidity waters of the order of 6.5 uT by analyzing the particle size distribution using aluminum sulfate, ferric chloride and polyaluminum chloride (PAC) as coagulants under different shear rate in slow mixing. This evaluation was done through image analysis and it can be concluded that the flocculation process can, in fact, be divided into a transition stage, when the flocs grow until reaching their maximum value, and stabilization stage, when the distribution size and the equivalent diameter of the flocs do not vary significantly. In addition, for ferric chloride and PAC coagulants, the best flocculation efficiency was observed for shear rate of 60 s-1, suggesting that under conditions of low turbidity, it is important to provide a greater opportunity for particle collisions so that flocs to grow more effectively, especially for these coagulants whose flocs appear to have a higher resistance to breakage than those formed with aluminum sulfate. Finally, the coagulants showed similar performance when compared to the most favorable mixing intensities of each of them, with slightly better results for ferric chloride and PAC in relation to the average diameter of the flocs.